Fragmentaç\~ao internacional da produç\~ao e cadeias globais de valor - Flavio L. Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Production fragmentation - dispersion of the individual steps involved in the production of a particular good across different countries and several companies - means that the fabrication of an increasingly large number of goods is taking place in global value chains, with different patterns of geographic structure and governance, which have in common the fact that inputs, parts, services - that is, each step or task involved in the production of a final good - will take place wherever the materials and skills necessary for their completion are available, at competitive prices and quality. This phenomenon is opening new research agendas, and is changing the way the foreign trade statistics are compiled and used, with initiatives to produce trade data in value-added terms, since the use of gross trade data overestimates both the value of global trade and the exports from countries that produce final goods. On the other hand, this process has changed radically the political economy equilibrium of trade policy in the countries that participate in it, making trade policies of individual countries increasingly interdependent, reducing the incentive to adopt protectionist policies, and increasing the demand for a deepening of trade integration. International production fragmentation has also shown to be an opportunity for development, although there are risks involved, which highlight the importance of public policies in order to assure that a strategy which involves joining global value chains will translate into real benefits for a country.
Keywords: F02; F10; F23; 330; international production fragmentation; global value chains